AYUN-AYUN JO GALITIAK: EKSPRESI MUSIKAL DALAM BABIOLA PADA MASYARAKAT KABUPATEN PESISIR SELATAN - Kurniawan, Al Wahyu; Sastra, Andar Indra; Nursyirwan, Nursyirwan (Universitas Lancang Kuning, 2018)
This analysis entitled ''Ayun-ayun jo galitiak'' musical expression in Babiola in the society of Pesisir Selatan regency. It aims to show the musical expression in that Babiola by formulizing the empirical experience of the respondents. It is a qualitative analysis to explore the form of ayun-ayun jo galatik in the song of Sikambang. Data collecting is done by library research, observation, interview and documentation. The result shows that Ayun-ayun jo galatik has contour melody up and down in slow tempo with free rhythm the musical expression.